The Wounded Healer in Psychotherapy: A Systematic Literature Review Concerning an Issue Related to the Psychotherapeutic Relationship Interspersed With Illustrations From Clinical Practice - Torii, Shizuka (Auckland University of Technology, 2005)
This dissertation is concerned with the woundedness of the therapist and scrutinises (or rescrutinises) its potential value and possible uses in the service of healing others. The question addressed in this dissertation can be broken down to; (i) is the therapist's woundedness really useful in helping the client? (ii) how can the therapist use his/her own woundedness in the service of healing others? and (iii) with an acknowledgement of the therapist's vulnerability, is psychotherapy, as an old joke suggests, "when two people who need help get it"? The dissertation approaches these questions by carrying out a modified systematic review of literature pertinent to the topic. The main data base used is PsychINFO, which virtually contains PEP (Psychoanalytic Electronic Publishing). The literature included in this dissertation is largely theoretical and clinical with the addition of two empirical studies. The themes identified as a result of studying the selected and located literature include the paradigm of the wounded-healer and the intersubjectivity of psychotherapeutic relationship, which are discussed in the chapters 2 and 3 respectively. Following these, Chapter 4 presents clinical vignettes to illustrate some of the points made in the review of literature. The dissertation clarifies two important distinctions; one between wounded and impaired on the therapist's part, and the other between asymmetry and mutuality in the therapeutic relationship, which help demystify and justify wounded-healing as effective psychotherapy. It concludes that the therapist's woundedness has wonderful potential for therapeutic effectiveness when the therapist has integrated his/her woundedness. On the level where the psychotherapeutic process is mutual, it is important for the psychotherapist to relate to the client as one human being to another, recognising his/her own emotional needs, conflicts, and dynamics similar to those of the client. Besides those approximations to the research questions, this dissertation achieves a successful marriage between Jungian and intersubjective theories, indicating that the two can contribute to each other fruitfully.
Keywords: Psychotherapy; Psychotherapist and patient